Attentional strategy choice is not predicted by cognitive ability or academic performance. Issue 10 (26th November 2022) - McKinney, Molly R.; Hansen, Heather A.; Irons, Jessica L.; Leber, Andrew B.
ABSTRACT: People exhibit vast individual variation in the degree to which they choose optimal attentional control strategies during visual search, although it is not well understood what predicts such variation. In the present study, we sought to determine whether markers of real-world achievement (assessed via undergraduate GPA) and cognitive ability (e.g., general fluid intelligence) could predict attentional strategy optimization (assessed via the Adaptive Choice Visual Search task; [Irons, J. L., & Leber, A. B. (2018). Characterizing individual variation in the strategic use of attentional control. Journal of Experimental Psychology: Human Perception and Performance, 44 (10), 1637–1654]). Results showed that, while general cognitive ability predicted visual search response time and accuracy, neither achievement nor cognitive ability metrics could predict attentional strategy optimization. Thus, the determinants of attentional strategy remain elusive, and we discuss potential steps to shed light on this important research topic.